The influence of facilities and destination image on tourist loyalty and satisfaction of ladaya attractions in kutai kartanegara district (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
This study aims to determine whether the destination facilities and images partially have a significant effect on tourist satisfaction, whether the destination facilities and images partially have a significant effect on tourist loyalty, knowing the significant effect of tourist satisfaction on tourist loyalty, and knowing the effect of facilities on tourist loyalty through tourist satisfaction as an intervening variable and knowing the influence of destination image on tourist loyalty through tourist satisfaction as an intervening variable. This type of research is explanatory research with a quantitative approach. Data were collected using questionnaires distributed to tourists visiting Ladaya tourism objects using simple random sampling technique. Variable measurement uses a Likert scale. The population amounted to 268,433 and a sample of 100 respondents was determined using the sampling formula from Slovin. Data analysis used is the classic assumption test, regression analysis, path analysis and Sobel test. Regression analysis was carried out with the SPSS version 24 program. The results showed that facilities had a significant positive effect on tourist satisfaction, destination image had a significant negative effect on tourist satisfaction, tourist satisfaction had a significant positive effect on tourist loyalty, facilities had no significant effect on tourist loyalty, the image of detention had a significant negative effect on tourist loyalty, facilities had no effect towards tourist loyalty through tourist satisfaction and destination image has no effect on tourist loyalty through tourist satisfaction. Based on the sobel test it is known that there is no mediating effect of tourist satisfaction variables on the influence of facility variables and destination image on tourist loyalty.